Optimization of protein requirements and feed restriction in Penaeus vannamei (Boone, 1931) biofloc culture - S. Ferrando-Juan; J. Gómez-Aguilera; S. Martínez-Llorens; A. Tomás-Vidal; M. Rodilla; M. Jover-Cerdá; F. J. Moyano; D. S. Peñaranda (Aquaculture International, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Permian thermally-induced shear of the Cossato-Mergozzo-Brissago shear zone in the W-Southalpine basement, Italy: new petrological, geochemical and U–Pb geochronological constraints from the amphibolite-facies units of the Strona Ceneri Border Zone - F. Arboit; A. Decarlis; S. Ferrando; A. Maffeis; S. De Bernardi; A. Ceriani (International Journal of Earth Sciences, 2024)

Linking processing to formulation in dynamic membranes of tunable pore size for lemon oil emulsions - W. Kaade; M. Ferrando; S. de Lamo-Castellví; C. Güell (Journal of Food Engineering, 2023)

Fields with no recent legume cultivation have sufficient nitrogen-fixing rhizobia for crops of faba bean (Vicia faba L.) - Marta Maluk; Francesc Ferrando-Molina; Laura Lopez del Egido; Adrian Langarica-Fuentes; Genet Gebre Yohannes; Mark W. Young; Peter Martin; Richard Gantlett; Greg Kenicer; Cathy Hawes; Graham S. Begg; Richard S. Quilliam; et al. (Plant and Soil, 2022)
Purpose (1) To assess the biological N fixation (BNF) potential of varieties of faba bean ( Vicia faba L.) cropped with or without compost in an experimental field-scale rotation with no recent history of legumes, (2) to enumerate soil populations of Rhizobium leguminosarum sv. viciae ( Rlv ), and to genetically characterize the nodulating Rlv strains, (3) compare BNF with other sites in Britain. Methods BNF was evaluated from 2012 to 2015 using 15 N natural abundance. Treatments were either PK fertilizer or compost. Soil rhizobial populations were determined using qPCR, the symbiotic rhizobia genotyped (16 S rRNA, nodA and nodD genes), and their BNF capacity assessed ex situ . The reliance of legumes on BNF at other British sites was estimated in a single season, and their nodulating symbionts examined. Results Faba bean obtained most of its N through BNF (>80%) regardless of variety or year. N-accumulation by cvs Babylon and Boxer increased with compost treatment in 2014/2015. Rhizobial populations were c. 10 5 -10 6 Rlv cells g −1 soil regardless of field or treatment. 157 Rlv microsymbionts grouped into two large nodAD clades; one mainly from V. faba , and the other from various legumes. All isolates nodulated, and some performed better than commercial inoculant strains. Conclusions Faba bean can provide most of its nitrogen through BNF and leave economically valuable residual N for subsequent crops. Recent legume cropping in northern Europe is not essential for effective nodulation: rhizobia may persist in a range of farmland locations. Nevertheless, there is the potential to apply elite rhizobial strains as inoculants in some soils.

Midtrophic fish feeding modes at the poles: an ecomorphological comparison of polar cod (Boreogadus saida) and Antarctic silverfish (Pleuragramma antarctica) - Erica Carlig; Jørgen S. Christiansen; Davide Di Blasi; Sara Ferrando; Eva Pisano; Marino Vacchi; Richard L. O’Driscoll; Laura Ghigliotti (Polar Biology, 2021)
The polar cod (Boreogadus saida ) and the Antarctic silverfish ( Pleuragramma antarctica ) are pelagic fish endemic to the Arctic and Antarctica sea, respectively. Both species are abundant and play a central role as midtrophic wasp-waist species in polar ecosystems. Due to their biological and ecological characteristics (small size, complex life histories, relatively short generation cycles, movement capability, planktivorous diet, and importance as prey), the polar cod and the Antarctic silverfish are potentially good sentinels of ecosystem change. Changes in polar zooplankton communities are well documented. How changes impact ecosystems as a whole largely depend on the degree of diet specialization and feeding flexibility of midtrophic species. Here, we provide the ecomorphological characterization of polar cod and Antarctic silverfish feeding performances. A comparative functional ecology approach, based on the analysis of morpho-anatomical traits, including calculation of suction index and mechanical advantage in jaw closing, was applied to profile the feeding modes and flexibility of the two species. Ecomorphological evidence supports differences in food acquisition: the polar cod appears able to alternate particulate ram-suction feeding to a pump filter feeding, and the Antarctic silverfish results be both a particulate ram and a tow-net filter feeder. Both species exhibit opportunistic feeding strategies and appear able to switch feeding mode according to the abundance and size of the available prey, which is a clue of potential resilience to a changing environment.

Parameter optimization for creating reliable photogrammetric models in emergency scenarios - S. Gagliolo; R. Fagandini; D. Passoni; B. Federici; I. Ferrando; D. Pagliari; L. Pinto; D. Sguerso (Applied Geomatics, 2018)

Vacchi's palatal organ: a widespread trait in Holocephali - B. Finucci; L. Gallus; A. Amaroli; S. Candiani; M. Rottigni; M. A. Masini; S. Ferrando (Journal of Fish Biology, 2018)
A palatal organ, possibly used for food sorting and processing, has previously been identified among the vomerine toothplates of the chimaeroid Chimaera monstrosa . In this study, the palatal organ was described in six additional species, confirming it is a widespread trait among holocephalans. It is proposed that this palatal structure, which appears to differ in shape according to each chimaeroid's degree of durophagy and is not homologous to the palatal structure described in teleosts, be hereby referred to as Vacchi's organ.

Lithospheric magma dynamics beneath the El Hierro Volcano, Canary Islands: insights from fluid inclusions - E. Oglialoro; M.L. Frezzotti; S. Ferrando; C. Tiraboschi; C. Principe; G. Groppelli; I.M. Villa (Bulletin of Volcanology, 2017)

Gross morphology and histology of the olfactory organ of the Greenland shark Somniosus microcephalus - S. Ferrando; L. Gallus; L. Ghigliotti; M. Vacchi; J. Nielsen; J. S. Christiansen; E. Pisano (Polar Biology, 2016)

Taxonomic and Functional Resilience of Grasshoppers (Orthoptera, Caelifera) to Fire in South Brazilian Grasslands - C P R Ferrando; L R Podgaiski; M K M Costa; M D S Mendonça (Neotropical Entomology, 2016)

Fragments of the Western Alpine Chain as Historic Ornamental Stones in Turin (Italy): Enhancement of Urban Geological Heritage through Geotourism - A. Borghi; A. d’Atri; L. Martire; D. Castelli; E. Costa; G. Dino; S. E. Favero Longo; S. Ferrando; L. M. Gallo; M. Giardino; C. Groppo; R. Piervittori; et al. (Geoheritage, 2014)

Theba pisana (Müller, 1774) (Gastropoda, Helicidae) and other alien land molluscs species in Argentina - Alejandra Rumi; Julieta Sánchez; Noelia S. Ferrando (Biological Invasions, 2010)

Population genetic structure and distribution of introduced American mink (Mustela vison) in Spain, based on microsatellite variation - Roberta Lecis; A. Ferrando; J. Ruiz-Olmo; S. Mañas; X. Domingo-Roura (Conservation Genetics, 2008)

Composition and thermal structure of the lithosphere beneath the Ethiopian plateau: evidence from mantle xenoliths in basanites, Injibara, Lake Tana Province - S. Ferrando; M. L. Frezzotti; E.-R. Neumann; G. De Astis; A. Peccerillo; A. Dereje; Y. Gezahegn; A. Teklewold (Mineralogy and Petrology, 2008)

Na + /K + ATPase immunoreactivity in olfactory epithelium of small‐spotted catshark Scyliorhinus canicula (L.): possible presence of ion exchanging cells? - S. Ferrando; M. Bottaro; L. Gallus; L. Girosi; M. Vacchi; G. Tagliafierro (Journal of Fish Biology, 2006)
Na + /K + ATPase immunoreactivity in olfactory epithelium of Scyliorhinus canicula was localized in well featured light large cells. It was distributed in the basolateral membranes as reported in the literature for typical ion exchanging cells.

Melanism in the gastric mucosa of the scalloped ribbonfish from the Ligurian Sea - M. Bottaro; S. Ferrando; T. Ferrando; P. N. Psomadakis; M. Vacchi (Journal of Fish Biology, 2005)
Internal stomach melanism was observed in two scalloped ribbonfish Zu cristatus from the Ligurian Sea. The phenomenon may help prevent advertizing the presence of this species after consumption of bioluminescent prey.